The financial evaluation of transportation project in Malaysia: a case study of Putrajaya monorail transit system - Alias, A.; Wan Yusoff, W.Z.; Abdul Samad, Z. (2009)
This paper explores a financial evaluation of the proposed transportation project of the Putrajaya Transit System Line 1 (PMT1) in term of investment return to the concessionaire. One of the key elements in the planning of Putrajaya is to provide an efficient transportation system befitting a city design for the 21st century. The formation of transportation strategy has to be undertaken with a view to satisfying as far as possible, free of congestion and has minimal levels of air and noise pollution. In relation to this, most of the concessionaires are ambivalent about assessing the worth of investment return with regards to infrastructure project because of the multi-faceted issues involved in evaluation of such investment. Thus, an adjusted financial evaluation is introduced with application of Discounted Cash Flow (DCF), Net Present Value (NPV) and Internal Rate of Return (IRR) as main tools to evaluate the project. This approach is applied to prove the financial viability and feasibility of PMT1 project according to respective proposed business plan. Therefore, the concessionaire is able to evaluate the profitability and the possibility of investing in this type of concession project.